Estado nutricional en los niños de 0 a 5 años pertenecientes al CNH rincón mágico gotitas de ilusión de la ciudad de Loja durante el periodo agosto diciembre 2016 - Bravo Maldonado, Maria Gabriela (2018)
Abstract: To determine the nutritional state of children aged 0-5 years old, pertaining to CNH "Rincón Mágico Gotitas de Ilusión" during August December 2017, this study ws mde with a quantitative focus, descriptive- transversal type. This study focused on a sample of 60 children and determined: weight, size, IMC, and hemoglobin; the facts they analyzed according to the standardized curves of OMS in 2005 (Z-score) and the criterion refers to the OMS for the values of hemoglobin (mg/dl). Finally, the results were calculated in Excel and in the program SPSS 21, through these programs the nutritional state of the sample was determined. 28.3% of the evidence presented some level of anemia, being more evident in males and on classifying them, 5% presented slight anemia and 23.3% had moderate Anemia. On the other side, 75% had an adequate nutritional state, 10% presented slight malnutrition, 8.33% overweight and 6.67% were obese. Finally, they observed that there was a correlation between the nutritional state and the values of hemoglobin.